Ecuaciones de sintonización para controladores difusos basadas en modelos de primer orden más tiempo muerto (2011)
Fuzzy Logic Controllers (FLC) has been effective dealing with high non–linear processes or those whose mathematical model is difficult to obtain. Nevertheless FLC stability and performance depend on suitable adjustment of its tuning parameters; up to date, the tuning process has used a trial and error approach. This paper presents a set of FLC tuning equations based on dynamical process response identification as a First Order Plus Dead Time (FOPDT) model. The FLC tuning equations obtained reduce design time.